PENGARUH WORKING CAPITAL TO TOTAL ASSET, DEBT TO EQUITY RATIO, OPERATING INCOM TO TOTAL LIABILITIES, TOTAL ASSET TURNOVER, INVENTORY TURNOVER DAN NET PROFIT MARGIN TERHADAP PERTUMBUHAN LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa - Jelita Mardiana Prihani, 14.05.52.0204; Lisiantara, G. Anggana (Students' Journal of Accounting and Banking, 2019)
This study aims to examine and analyze the Working Capital to Total Asset (WCTA), Debt to Equity Ratio (DER), Operating Income to Total Liabilities (OITL), Total Asset Turnover (TATO), Inventory Turnover (ITO), and Net Profit Margin (NPM) of Profit Growth in Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2015-2017 Period. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) and published financial statements from 2015 to 2017. This research is an empirical study using a purposive sampling technique in sampling. The analytical tool used is normality test, classic assumption test, multiple linear regression test, model test and hypothesis test. Based on the research that has been conducted, the results of this study show that the Operating Income to Total Liabilities (OITL), Total Asset Turnover (TATO), Inventory Turnover (ITO) has a significant effect of Profit Growth. While Working Capital to Total Asset (WCTA), Debt to Equity Ratio (DER) and Net Profit Margin (NPM) have no significant effect of Profit Growth.